Hubungan Kecerdasan Emosional Terhadap Hasil Belajar IPA Siswa Kelas V SD Nur Fadhilah Medan Tahun Ajaran 2022/2023 - Nasution, Nisa Aulia; Ananda, Lala Jelita; Perangin Angin, Laurensia Masri; Simanihuruk, Lidia; Pandimun Ambarita, Dody Feliks (Universitas Labuhanbatu, 2023)
This research was conducted with the aim of knowing the relationship between emotional intelligence and science learning outcomes for fifth grade students at SD Nur Fadhilah Medan, Academic Year 2022/2023. The type of research used is correlational research with quantitative research methods. The sample in this study were fifth grade students at SD Nur Fadhilah, Medan Marelan District, Medan City Regency, totaling 110 people. Data collection techniques in this study were questionnaires or questionnaires and science learning outcomes. Questionnaire data collection instrument with a two-point Guttman Scale for each answer. Based on the results of the correlation of the relationship between the variable emotional intelligence (X) on science learning outcomes (Y) with a correlation coefficient of 0.087 with a very low level of relationship category, while from the list r obtained rtable of 1.874 at Î± = 0.05, then rcount < rtable (0.087 <1.874). So it can be concluded that emotional intelligence has no significant relationship to the science learning outcomes of fifth grade students at SD Nur Fadhilah Medan with the result of the coefficient of determination between variables that is 8%.